Water stable molecular n-doping produces organic electrochemical transistors with high transconductance and record stability - Alexandra F. Paterson (Nature Portfolio, 2020)
Improving electron transport and stability of n-type organic electrochemical transistors (OECTs) is required to realize a commercially-viable technology for bioelectronics applications. Here, the authors report water-stable doped n-type OECTs with enhanced transconductance and record stability.